2002
DOI: 10.1124/jpet.102.036053
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Chronic and Spontaneous Intestinal Inflammation with an Antisense Oligonucleotide (ISIS 9125) to Intracellular Adhesion Molecule-1 in the HLA-B27/β2 Microglobulin Transgenic Rat Model

Abstract: Adhesion molecules are known to be an important part of leukocyte migration and extravasation in both homeostatic and inflammatory conditions. Intracellular adhesion molecule-1 (ICAM-1 or CD54) is constitutively expressed on endothelial cells and is up-regulated during acute and chronic inflammation. We investigated the efficacy and consequences of interfering with CD54 after administration of an antisense oligonucleotide to ICAM-1 (CD54) in the transgenic HLA-B27/␤2 microglobulin rat model. One hundred percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The early-increased transcripts, ICAM-1 and CINC-1, encode for proteins involved in initiating inflammation via recruitment and retention of leucocytes and neutrophils (25,26). The importance of ICAM-1 in IBD has been well characterized (45,46). ICAM-1 is constitutively expressed on the surface of endothelial cells, and in CUC, ICAM-1 levels increase concomitantly with inflammation (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…The early-increased transcripts, ICAM-1 and CINC-1, encode for proteins involved in initiating inflammation via recruitment and retention of leucocytes and neutrophils (25,26). The importance of ICAM-1 in IBD has been well characterized (45,46). ICAM-1 is constitutively expressed on the surface of endothelial cells, and in CUC, ICAM-1 levels increase concomitantly with inflammation (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…This is useful for drug delivery to the GI epithelium for prophylactic interventions, or across this barrier for delivery to other sites. ICAM-1 expression is high in colorectal carcinoma, inflammatory bowel disease, Crohn’s disease, ulcerative colitis, bacterial infections, and other conditions [15, 3941]. Hence, ICAM-1 targeting also holds promise for therapeutic applications for these maladies.…”
Section: Discussionmentioning
confidence: 99%
“…Our open‐label, proof‐of‐concept trial explored the potential therapeutic benefit of ISIS 2302 in patients with chronic, unremitting pouchitis. A 60‐mL, 240‐mg enema formulation of ISIS 2302 was selected on the basis of animal studies, which predicted local tissue concentrations within the range shown to be effective in animal pharmacology models of inflammatory bowel disease 6 . A 6‐week duration of therapy was chosen on the basis of ongoing clinical trials in patients with active ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%